An Introduction to Stochastic Modeling / International Edition - Karlin Samuel; Taylos Howard M (Allyn And Bacon, 1984)
Preface, Introduction, Conditional Probability and Conditional Expectation, Markov Chains: Introduction, The Long Run Behavior of Markov Chains, Poisson Prcesses, Continuous Time Markov Chains, Renewal Phenomena, Branching Processes and Population Growth, Queueing Systems, Further Readings, Solutions to Selected Problems, Index.